Imperatives of Physical Exercise for a Healthy Living - Marjorie, Agu (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
This work focused on imperatives of physical exercise for a healthy living. Physical exercise is involving in regular activities with reduced sitting times, that enhances health, by improving the physiological functioning of the body which lowers risk of diseases. The paper identified some of the imperatives of physical exercise to be prevention of diabetes and heart diseases, reduces high blood pressure and generally, adds years to a persons life. So whether one is healthy or have medical issues, moderate activity is safe most for people and does a lot to improve the health, The paper concluded that lifestyle intervention such as promotion of physical activity in populations would result in significant improvements in health outcome. Therefore, recommended among others that during the daytime, all age groups should minimize the amount of time spent sitting (being sedentary).